Packaging Innovation of Local Product Fermentation of Kania Dairy Farmers Group in Tajur Halang Village, Cijeruk, Bogor - Meilisha Putri Pertiwia (International Journal of Quantitative Research and Modeling, 2020)
Community service program (PKM) for packaging innovation of local product fermentation of Kania Diary Farmers Group in Tajur Halang Village, Cijeruk Subdistrict, Bogor Regency has been conducted. It was held from April to Juli 2019. It aimed to empower Kania Diary Farmers Group in innovating milk fermentation product, introducing nutrition fact of es mambo kefir, and introducing well-packaged product. Its method were literature studied for an interesting packaging, field obeservation, kefir mambo ice production, nutrition analysed using proximat analysis, explanation about nutrition facts, implementation well-packaging, and discussion between instructors and Kania Group. After analysing the kefir mambo ice, it yielded 35 cal for 50 g/serving. It also contained 1 g protein, 1.5 g fat, and 1 g carbohydrate for 35 g/serving. All the nutrition containing in kefir mambo ice is good for a healthy body. Kania group members looked so enthusiasm and excited during the training. Hopefully, through this training, Kania group will develop better pacakaging for every single of its product.